Impact of 12 weeks of robotic walking on contracture and spasticity in children with cerebral palsy - Kiran Isapure (CMBES Proceedings, 2024)
Introduction Cerebral palsy (CP) is the most common cause for physical disability in children and is a result of a lesion of the developing brain [1]. Most children with CP have muscle contracture and spasticity. Spasticity is defined as a velocity-dependent increase in tonic stretch reflexes to phasic stretch, in the absence of voluntary activity and contracture is defined as a pathological condition that causes stiffness, resistance to movement and reduced range of motion in joints [2]. Both contracture and spasticity contribute to resistance to movement. Recently robotic devices have increasingly been utilized to provide the experience of walking [3]. In doing so, they provide repeated voluntary or passive knee extensions and thus may help reduce contracture and/or spasticity. We aim to evaluate the impact of 12 weeks of robotic walking on muscle contracture and spasticity in children with CP. Methods Six participants (3 females, 3 males, age 5-24 years) with severe CP (Gross Motor Function Classification System IV-V), who were unable to walk independently, underwent 12 weeks of robotic walking. Passive ramp-and-hold knee extensions were performed at two speeds (10°/sec and 30°/sec) using a Biodex dynamometer before and after training. Limb weight at each position was measured during 10°/sec stretches that had no muscle activity. The limb weight was subtracted from the torques recorded at 30 deg/s. Torque at 30° knee flexion was measured. Muscle Stiffness was calculated as change in torque/degree from 60° to 30°knee flexion. Figure 1: Change in Muscle stiffness and Torque at 30° knee flexion. After 12 weeks of robotic walking, participants showed significant reduction in muscle stiffness(p=0.031). While a consistent reduction in torque at 30° knee flexion was observed, it did not reach statistical significance(p=0.0625). Conclusion Our results suggest that robotic walking may show reductions in spasticity and contracture in children with CP. Additional testing should be completed to make conclusions. References Rosenbaum, Peter et al. “A report: the definition and classification of cerebral palsy April 2006.” Developmental medicine and child neurology. Supplement vol. 109 (2007): 8-14. Lance JW. The control of muscle tone, reflexes, and movement:Robert Wartenberg Lecture. Neurology 1980;30:1303–131. Morone, Giovanni et al. “Clinical features of patients who might benefit more from walking robotic training.” Restorative neurology and neuroscience vol. 36,2 (2018): 293-299. doi:10.3233/RNN-170799